2010
DOI: 10.1002/dc.21203
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathologist‐performed ultrasound‐guided fine‐needle aspiration of parathyroid lesions

Abstract: The gold standard to determine the cause of primary hyperparathyroidism (PHPT) is bilateral neck exploration. As most cases are caused by parathyroid adenoma, there is a movement toward preoperative localization of the abnormal gland by ultrasound and/or Tc(99)-sestamibi scan and minimally invasive parathyroidectomy. Nonpalpable thyroid nodules are common and cannot be differentiated from parathyroid lesions by imaging alone. This study examines cytopathologist-performed ultrasound-guided fine-needle aspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 17 publications
0
35
0
1
Order By: Relevance
“…Study material was obtained by ultrasound-guided fine-needle aspiration biopsy (UG-FNA) performed by a clinical cytologist (interventional cytologist) [11], who also performed cytomorphological analysis of the material obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study material was obtained by ultrasound-guided fine-needle aspiration biopsy (UG-FNA) performed by a clinical cytologist (interventional cytologist) [11], who also performed cytomorphological analysis of the material obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Occasionally, it may be necessary to perform FNA of more than one suspect mass, frequently from several sites. Parathyroid cyst FNA generally yields clear, colorless, water-like or golden-brown fluid [1,2,7,11,13,[25][26][27]. Aspirate sediment should be examined on a microscope, along with determination of aspirate PTH.…”
Section: Disclosurementioning
confidence: 99%
“…Some authors suggested that FNA is valuable in patients who have a nondiagnostic Tc 99 -sestamibi scan, with multiple enlarged parathyroid glands, prior failed surgery, differentiating parathyroid adenomas from posterior thyroid nodules, atypical location, and nonfunctioning parathyroid incidentalomas (Abraham, Duick et al 2008;Vu and Erickson 2010). Cellular FNA specimens with features not typical for thyroid lesions should be triaged for PTH assay in the FNA rinse, which is useful to differentiate parathyroid lesions from thyroid lesions (Owens, Rekhtman et al 2008;Ciuni, Ciuni et al 2010;Lieu 2010). This technique is also used during operation (Lamont, McCarty et al 2005).…”
Section: Clinical Workup Of Parathyroid Lesionsmentioning
confidence: 99%
“…The ultrasound images demonstrate a cystic lesion. FNA aspirates clear liquid, which should be sent to chemistry laboratory to test PTH level (Absher, Truong et al 2002;Ciuni, Ciuni et al 2010;Lieu 2010). The first treatment is the aspiration FNA, which can be curative, but recurrences can be treated surgically (Ciuni, Ciuni et al 2010).…”
Section: Fine Needle Aspiration Biopsy Of Parathyroid Lesionsmentioning
confidence: 99%
See 1 more Smart Citation